Brand therapy : 15 techniques for creating brand strategy in pharma and medtech - Smith, Brian D. (Great Britain : Practical Inspiration Publishing, 2018)
Brand Therapy is a (3z(Bhow to(3y (Bbook for brand teams in the pharma and medtech sectors. It describes when and how to use a selection of strategic planning tools.s
Introduction -- Chapter 1: Strong brand strategies use the right tools: An overview of the brand team$1 (Bs toolkit -- Chapter 2: Strong brand strategies are about the customer: Using the Customer-Centric Market Definition to frame your analysis. -- Chapter 3: Strong brand strategies are decisive: Using Drucker$1 (Bs Definition to clarify your brand strategy -- Chapter 4: Strong brand strategies are tested: Using Brand Strategy Diagnostics to test and improve your strategy -- Chapter 5: Strong brand strategies are aligned to the market: Using SWOT Alignment to guide your brand strategy. -- Chapter 6: Strong brand strategies are based in reality: Using Reality Filters to gain strategic objectivity -- Chapter 7: Strong brand strategies are focused: Using the Focus Matrix to guide complex strategies -- Chapter 8: Strong brand strategies are your own: Using Value Chain Comparison to identify your firm$1 (Bs distinctive strengths and weaknesses. -- Chapter 9: Strong brand strategies overcome the competition: Using Competitive Pressure Analysis to identify competitive threats and opportunities -- Chapter 10: Strong brand strategies understand the customer: Using Contextual Segmentation to identify opportunities and threats from customer differences. -- Chapter 11: Strong brand strategies compete in the future: Using Emergent Properties Analysis to identify future opportunities and threats -- Chapter 12: Strong brand strategies anticipate the market: Using the Product Category Life Cycle to predict customer and competitor behaviour. -- Chapter 13: Strong brand strategies are built on insight: Using the Hypothesis Loop to see what your competitors don$1 (Bt -- Chapter 14: Strong brand strategies create value: Using the Concentric Value Proposition to translate strategy into activities. -- Chapter 15: Strong brand strategies are measured: Using 3L Metrics to improve brand strategy implementation. -- Chapter 16: Strong brand strategies are understood: Using the Wedge Brand Plan Structure to communicate your brand strategy.s
Keywords: PHARMACEUTICAL INDUSTRTY -- MARKETING